Optimasi Formula Sirup Ekstrak Etanol Daun Sukun (Artocarpus altilis) Dengan Pemanis Sorbitol dan Co – Solvent Propilen Glikol - Nurul Hidayati; Ivan Nuryanto; Saifudin Zukhri (CERATA Jurnal Ilmu Farmasi, 2019)
Breadfruit leaves (Artocarpus altilis) are effective in reducing high blood sugar levels. One of the uses of breadfruit is by making it into syrup. The manufacture of breadfruit leaf ethanol extract is expected to improve the bitter taste of breadfruit leaves. This study aims to determine the effect of variations of sorbitol and propylene glycol and to obtain the optimum value of sorbitol and propylene glycol on the physical properties and hedonic value of syrup preparations. Breadfruit leaveswas extracted by multilevel maceration with 70% ethanol. Thick breadfruit leaf extract made syrup preparations in 5 runs with variations of sorbitol: propylene glycol, namely Run 1 (20%: 25%), Run 2 (35%: 10%), Run 3 (31.25%: 13.75% ), Run 4 (27.5%: 17.5%) and Run 5 (23.75%: 21.25%). The syrups were tested for their physical properties including organoleptic, viscosity, pH and hedonic tests. The test results are optimized with Simplex Lattice Design. The optimum formula of the predicted results is verified by analysis of one sample t-test with a 95% confidence level.The results showed an increase in sorbitol and propylene glycol increased the pH and hedonic values but did not affect the viscosity value of syrup preparations. Sorbitol concentration of 30,0005% and propylene glycol 14.9995% produced syrup with pH and hedonic value optimum differed insignificantly with p-values> 0.05.